Mapping metabolite change in the mouse brain after esketamine injection by ambient mass spectrometry imaging and metabolomics - Liu, Guan-Xi; Li, Ze-Lin; Lin, Su-Yan; Wang, Qian; Luo, Zheng-Yi; Wu, Kai; Zhou, Yan-Lin; Ning, Yu-Ping (Frontiers in Psychiatry, 2023)
Ketamine as a new, fast, and effective antidepression method, the possible dissociation effect, sensory changes, abuse risk, and the inability to accurately identify whether patients have a significant response to ketamine limit its clinical use. Further exploring the antidepressant mechanism of ketamine will contribute to the safe and practical application of ketamine. Metabolites are the products of upstream gene expression and protein regulatory networks, play an essential role in various physiological and pathophysiological processes. The traditional metabonomics is difficult to achieve the spatial localization of metabolites, which limits the further analysis of brain metabonomics by researchers. Here, we used a metabolic network mapping method called ambient air flow-assisted desorption electrospray ionization (AFADESI)- (Mass spectrometry imaging) MSI. We find the main change in glycerophospholipid metabolism around the brain and the sphingolipid metabolism changed mainly on pallidal-which shows the most significant metabolite change. The spatial distribution of metabolic changes was evaluated in the whole brain, and the potential mechanism of s-ketamine’s antidepressant effect was explored in this research.